Unrepresented accused persons in the lower courts / Lim Heng Seng - Lim , Heng Seng (1975)
The elaborate substantive, evidentiary and procedural provisions in the area of criminal justice, i.e., the law of crimes and the administration of criminal justice, are the result of the balance achieved by the interaction of the forces tending to the protection of society and those to the safeguarding of individual liberty. The resolution of these competing interests ultimately depends on what weight and importance is attached to either and this is determined by the general notions of fairness and justice and the existing circumstances of the country.